Analisis Prospek Bank Syariah Dan Lembaga Keuangan Islam Dalam Memasuki Pasar Negara Inggris - Iwan Fahri Cahyadi (IAIN Kudus, 2018)
Globalization is a great business opportunity for the company Multi National Corporation (MNC) and Trans National Corporation (TNC) for expanding his business. Change the direction of economic policy, in particular the Shariah-based business that provides an opportunity for Islamic banking and Islamic financial institutions to expand his business in continental Europe, especially in the United Kingdom. The purpose of the research was to find out, the strategy of Islamic banks and Islamic financial institutions to enter the market in the United Kingdom and prospeknya countries in the foreseeable future. The research method used is qualitative diskriptif fenomenalogi approach i.e. we allow qualitative researchers implement and apply subjective abilities and exploratory process in interpersonalnya. As for the source of the data retrieved from the data of the secondary data source i.e. who do not directly provide data to a data gatherer, e.g. documents, journals, research, books, and Government regulations.The results showed that the market in the countries of United Kingdom Islamic business very promising in the future given the growth of the Muslim population from year to year are experiencing significant increase and economic growth in the United Kingdom